The Implementation of Safeguard In Efforts to Protect Domestic Industrial Products - Muhammad Sood; Djumardin Djumardin; Ufran Ufran (Fakultas Hukum Universitas Mataram, 2021)
Trade security measures (safeguards) are government policies of importing countries to recover serious losses or prevent the threat of serious losses to domestic industries as a result of a surge in imports of similar goods are directly competitive. The purpose of this study is to analyze safeguard regulation in international trade, and to analyze the implementation of safeguards to protect domestic industries. This research is a normative legal research with a statute approach, a conceptual approach and a comparative approach. The technique of collecting legal materials is conducted by literature study. The analysis of legal materials was carried out in a qualitative descriptive manner. The results show that the safeguard arrangement is intended as a legal basis for the government to take security measures to recover serious losses and / or prevent the threat of serious losses from the domestic industry as a result of a surge in imports of similar goods which are directly competitors to domestic industrial products. The implementation of safeguards by importing countries is carried out by the Trade Safeguard Committee through stages, namely starting from investigation and evidence, determining the existence of a loss or threat of loss, and implementing security measures.